In silico mutagenesis on active site residues of Acinetobacter haemolyticus lipase KV1 for improved binding to polyethylene terephthalate (PET) - Khairul Anuar, Nurul Fatin Syamimi; Abdul Wahab, Roswanira; Huyop, Fahrul; Normi, Yahaya M.; Oyewusi, Habeebat Adekilekun; Susanti, Evi (Taylor and Francis, 2024)
Polyethylene terephthalate (PET) pollution is an emerging environmental hazard because of its recalcitrance to degradation. This study proposes an in silico mutagenesis of LipKV1 from Acinetobacter haemolyticus for improved lipase-PET interaction, using the PET-degrading Thermobifida cutinase (TfCut2) as the structural benchmark. Results revealed that lid deletion on LipKV1 (LipKV1_LE) facilitated the entry of PET into the active site. The mutation of several predicted amino acids into alanine expanded the LipKV1 active site for better PET binding. Docking results indicated that the LipKV1_LE mutants, Var9 (-6.2 kcal/mol), Var18 (-6.0 kcal/mol), and Var181 (-6.0 kcal/mol), produced higher binding affinities with PET than the wild-type LipKV1 (-2.5 kcal/mol) and TfCut2 (-4.6 kcal/mol), attesting that the selected mutation sites played prominent role in altering the abilities of LipKV1_LE mutants to bind to PET. Our molecular dynamics (MD) simulation results corroborated the variant-PET complexes’ improved binding, mirrored by their improved conformations (RMSD ∼0.35 nm). The RMSF results also showed acceptable fluctuation limits of the LipKV1_PET mutant complexes (RMSF < 0.5 nm). Rg data of the complexes showed that they are conformationally stable, with a maximum of three H-bonds in their interaction with PET. SASA results showed that the mutations did not profoundly alter the hydrophobicity of the amino acid residues. MM-PBSA calculations on the LipKV1_PET mutant complexes estimated binding free energies between −28.29 kcal/mol to −23.25 kcal/mol, comparable to the molecular docking data. Thus, the MD data conveyed the practicality of the above-said site mutations in rationally designing the LipKV1 active site for better PET degradation.